2011
DOI: 10.1111/j.1740-8709.2011.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of complementary feeding indicators and associated factors in children aged 6–23 months across five South Asian countries

Abstract: Improving infant and young child feeding practices will help South Asian countries achieve the Millennium Development Goal of reducing child mortality. This paper aims to compare key indicators of complementary feeding and their determinants in children aged 6-23 months across five South Asian countries - Bangladesh, India, Nepal, Pakistan and Sri Lanka. The latest Demographic and Health Survey and National Family Health Survey India data were used. The analyses were confined to last-born children aged 6-23 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
183
21
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(280 citation statements)
references
References 10 publications
54
183
21
10
Order By: Relevance
“…This community based cross-sectional study identified the prevalence of dietary diversity feeding practice was 131 (23.3%) fed their child four or more varieties of foods and the rest 431 (76.7%) feed ≤3 food items from the seven food groups in 24 hour preceding the survey based on the WHO recommendation and indicators [26,28], the finding is higher than national prevalence which is 10.8% and relatively higher from recent study conducted in North Ethiopia Mekelle city which is 17.8% [29],and relatively lower than from finding from Nepalese (30.4%) [30].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This community based cross-sectional study identified the prevalence of dietary diversity feeding practice was 131 (23.3%) fed their child four or more varieties of foods and the rest 431 (76.7%) feed ≤3 food items from the seven food groups in 24 hour preceding the survey based on the WHO recommendation and indicators [26,28], the finding is higher than national prevalence which is 10.8% and relatively higher from recent study conducted in North Ethiopia Mekelle city which is 17.8% [29],and relatively lower than from finding from Nepalese (30.4%) [30].…”
Section: Discussioncontrasting
confidence: 50%
“…In general service utilization like growth monitoring, Post natal, Antenatal and institutional delivery enhance diversified feeding practice of mothers for their child because health professional give health education on importance of dietary diversity feeding practice during this service utilization [29,30,33].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used the general linear model for continuous outcomes and logistic regression for binary outcomes to estimate associations with the main explanatory variables. To facilitate comparisons of our results with results from a series of papers on a similar topic (33) , we defined main outcome as negative ('not meeting recommended feeding behaviour') and coded the statistical analyses according to the convention that an odds below 1 is a favourable and an odds above 1 is an unfavourable outcome.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Covariates Based on previous research on factors associated with infant and young child feeding practices (33) as well as determinants of child nutritional status in the context of Nicaragua (34) , the following indicators were selected as potential confounders: municipality, housing quality, food insecurity, women's education, women's age (years), child age (months), child sex and number of children under 5 years of age in the household. Housing quality was calculated using information on the quality of household construction, toilet facilities and sources of water and electricity.…”
mentioning
confidence: 99%
“…Lack of maternal knowledge and practices related to the importance of breast feeding and appropriate weaning practices and optimal hygienic behaviors often interfere with the proper care of children. [13][14][15] On the other hand, fathers as the household heads are the primary decision makers for the family, particularly in health care-seeking behaviors and use of health care facilities. In univariate analysis, we noted the associations between lack of formal schooling of both parents with intestinal amebiasis.…”
Section: Discussionmentioning
confidence: 99%